Telecollaboration and Linguistic Gains in Postsecondary Non-Native Portuguese Learning - MAIMONE, Luciane; ZACH, Ariel ZACH (The ESPecialist, 2022)
This study sought to investigate linguistic gains and crosslinguistic influence (CLI) from English and Spanish on the oral production of postsecondary L3 Portuguese learners, comparing the effects of two pedagogical approaches: oral synchronous telecollaboration between Portuguese learners and native speakers (Teletandem), and group work among learners in the L2 classroom. Participants met weekly for eight weeks, after which gains in oral proficiency were measured using an Elicited Imitation Task (EIT) and a listening comprehension test (LCT). Linguistic development was also measured by various indices of oral complexity, accuracy, and fluency (CAF). Results showed significant improvement in proficiency and all CAF measures over time, but no differences between groups. Spanish CLI was significantly higher than English CLI for both groups and the only type of CLI to significantly decrease. Participants' perceptions and beliefs, and the lack of differential performance across groups is discussed, considering different pedagogical and theoretical approaches to telecollaboration.